Cochlear implantation in X-linked deafness – How to manage the surgical challenges. (3rd July 2016) - Saeed, Haroon; Powell, Harry R. F.; Saeed, Shakeel R.
Abstract : Objective and importance : In children with X-linked deafness, cochlear malformations challenge the implant surgeon to avoid electrode insertion into the internal auditory meatus and prevent a continuous cerebrospinal fluid (CSF) leak. We describe our experience of cochlear implantation (CI) in two children with profound hearing loss secondary to X-linked deafness, highlighting safer operative techniques to avoid potential complications. Clinical presentation : Descriptive cases of two children with X-linked deafness (patient 1 and patient 2) undergoing CI. Peri-operative imaging and work-up to surgery are discussed. Specific operative considerations, post-operative complications and subsequent audiological performance are highlighted. Technique : In each case, intra-operative fluoroscopic imaging ensured intra-cochlear insertion of electrodes. Expected CSF gusher was seen in each case which was initially controlled by packing around the cochleostomy and array with temporalis muscle and fascia. Patient 1 developed post-operative meningitis secondary to continuous CSF leak. We avoided further significant CSF leak by planning staged procedures for patient 2, with obliteration of the middle ear cleft and external ear canal (EAC) at the time of implantation. In both patients, bilateral implantation successfully provided hearing thresholds of less than 35 dB in both ears at routine follow up. Conclusions : When planning for CI in children with radiological features of X-linked deafness, intra-operative imaging should be utilized to ensure correct electrode positioning. Traditional methods of stopping a CSF gusher may not suffice. We therefore encourage additional surgical obliteration of the middle ear space and EAC to avoid persistent CSF leak and its associated complications.